1997
DOI: 10.1021/jo9707848
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Biaryls via a Nickel(0)-Catalyzed Cross-Coupling Reaction of Chloroarenes with Arylboronic Acids

Abstract: The cross-coupling reaction of arylboronic acid with chloroarenes to give biaryls was carried out in high yields at 70-80 degrees C in the presence of a nickel(0) catalyst and K(3)PO(4) (3 equiv) in dioxane or benzene. The nickel(0) catalyst in situ prepared from NiCl(2).L (L = dppf, 2PPh(3)) (3-10 mol %) and 4 equiv of BuLi at room temperature was recognized to be most effective. The reaction can be applicable to a wide range of chloroarenes having an electron-withdrawing or an electron-donating group such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
126
2
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(138 citation statements)
references
References 37 publications
(45 reference statements)
8
126
2
2
Order By: Relevance
“…Essa inclinação positiva repete o resultado encontrado quando foi avaliada a influência dos grupos substituintes em para nos ácidos arilborônicos quando acoplados com tosilatos via catalisador NiCl 2 (PCy 3 ) 2 . Miyaura 15 reportou a investigação dos parâmetros de Hammett na reação de Suzuki de ácidos arilborônicos com 3-metoxiclorobenzeno catalisada por NiCl 2 (dppf). Ao montar o gráfico, constatou-se que as razões entre as bifenilas obtidas foram praticamente as mesmas, ou seja, o gráfico gerou uma reta.…”
Section: Resultsunclassified
“…Essa inclinação positiva repete o resultado encontrado quando foi avaliada a influência dos grupos substituintes em para nos ácidos arilborônicos quando acoplados com tosilatos via catalisador NiCl 2 (PCy 3 ) 2 . Miyaura 15 reportou a investigação dos parâmetros de Hammett na reação de Suzuki de ácidos arilborônicos com 3-metoxiclorobenzeno catalisada por NiCl 2 (dppf). Ao montar o gráfico, constatou-se que as razões entre as bifenilas obtidas foram praticamente as mesmas, ou seja, o gráfico gerou uma reta.…”
Section: Resultsunclassified
“…There is currently a great deal of interest in the coupling of aryl chlorides with arylboronic acids. [34] Although nickel catalysts are useful for this reaction as has been demonstrated by Indolese [35] and Saito et al, [36] most studies have focussed on palladium catalysts. Recently significant breakthroughs in this area have been made by Fu, [37] Buchwald, [38] Nolan, [39] Beller [40] and Trudell.…”
Section: Resultsmentioning
confidence: 99%
“…Due to the industrial interest in the functionalization of economically attractive aryl chlorides [7] there is currently a great deal of interest in the coupling of aryl chlorides with arylboronic acids. While Indolese [8] and Saito et al [9] demonstrated that nickel catalysts are useful for this purpose, most studies focussed on palladium catalysts. After initial work by us, [10] and others, [11] Fu, [12] Buchwald, [13] and Nolan [14] recently developed significant breakthroughs in this area.…”
Section: Introductionmentioning
confidence: 99%